Gleanings in Graveyards: A Collection of Curious Epitaphs - Norfolk, Horatio Edward (Salt Lake City, UT : Project Gutenberg, 2010)
"Gleanings in Graveyards: A Collection of Curious Epitaphs" by Horatio Edward Norfolk is a compilation of humorous and peculiar tombstone inscriptions written in the mid-19th century. This work serves as both an exploration and a celebration of the often whimsical nature of epitaphs found in graveyards across Great Britain, showcasing a variety of expressions that reflect the personalities of the deceased as well as the cultural attitudes toward death and remembrance. The opening of the collection presents an introduction to the topic, indicating that while British epitaphs may lack the elegance seen in other cultures, they compensate with a distinctive humor and charm. The preface outlines Norfolk's intent to amuse readers with a selection of epitaphs that range from sardonic and witty to poignant and sincere, reflecting a rich tapestry of human experiences and emotions. Following this, the book begins with a showcase of various epitaphs gathered from multiple locations, highlighting the unique stories and characteristics of those interred, whether through clever wordplay or heartfelt tributes. (This is an automatically generated summary.)
Release date is 2010-11-10
This ebook was transcribed by Les Bowler
Keywords: Epitaphs; Epitaphs -- Great Britain